IMPLEMENTASI GOOGLE SPREADSHEET DAN APPS SCRIPT DALAM SISTEM PENJADWALAN SIDANG TUGAS AKHIR PADA JURUSAN ENERGI DI POLITEKNIK XYZ - Musrinah; Andy Maulana Yusuf (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Departement of Energy of XYZ Polytechnic faces efficiency challenges in managing the final project trial schedule which is still conventional, so it is prone to schedule conflicts. This community service activity aims to implement a cloud-based scheduling information system using Spreadsheet and Apps Script to automate data validation. The implementation method includes partner needs analysis, database design, development of an 8-second filter logic script, and functional trials. The results of the activity show that this system is able to eliminate the potential for human error through automatic elimination features on the lecturer selection list and early warning notifications. This implementation has succeeded in significantly increasing the efficiency of scheduling time, from the original three days to only two hours. This system ensures data accuracy and facilitates transparent and real-time coordination between the final project coordinating lecturers involved.